Wartime Communication Shifts: Uncovering the Ukrainian Backlash to Amnesty International’s 2022 Report - Kobylinska,Iryna (2025)
A case study of Ukrainian backlash towards Amnesty International’s report that raises a higher question of decentralization of communication in international NGOs The study contributes to the application and development of crisis communication response strategies during major communication scandals. It focuses on global NGOs with localized international representation. Local branches are identified as key players in the communication decision-making process and are seen as cultural experts compared to the general offices of NGOs. The study aims to showcase and highlight the problem of using centralized messages and the negligence of cultural peculiarities. The study is especially applicable to international NGOs that report or observe events during military conflicts as it questions the crisis response strategy that Amnesty International applied after the ambiguous report “Ukraine: Ukrainian fighting tactics endanger civilians” on the 4th of August 2022. Qualitative content analysis is conducted to identify narrative patterns in the opinions of public stakeholders in the face of public activists, communication representatives, journalists, politicians, and online media in Ukraine. The results show that the depth and understanding of the culture in the produced apology is essential to demonstrate familiarity and involvement in the problem. The research contributes to the current understanding of reputational losses and should be considered an essential addition to the crisis communication handbook of international non-governmental organizations. The significance of the research lies in the importance of rearranging the communication plan techniques in international NGOs to address potential and ongoing crises. This master thesis suggests investing more resources into researching events that global non-governmental organizations are producing reports on, and taking the issue of credibility and validity of the produced messages more seriously to preserve the whole purpose of NGOs and ensure future funding.
Keywords: Reputation; Crisis communication; Framing theory; Media Framing; Public Backlash; International NGOs; Amnesty International; Military conflicts; War